THE ROLE OF LEADERSHIP AND GOVERNANCE ON INNOVATION AND RESEARCH IN KABARAK UNIVERSITY. - Gitahi, Samson; Koima, Dr. Joel (Kabarak University, 2016)
The progression and success of any institution is dependent on its adeptness to adapt to the diverse changes from global perspective. To cope with the changing expectations of the institutions, a culture that embraces innovation through research is required. The urge for institutions to embrace creativity, innovation and inventions has been necessitated by economic dynamics, to which contributing novel ideas enhances empowerment through leadership which in recent times has been central or strongly related to some of the world's most serious modern economic challenges. Economic growth alone does not lead to sustainable development since good leadership and governance must accompany. Institution management is the focal point in leadership and governance: This notion holds true while focusing on quality of research as a major factor which contributes significantly to institutional success.
Keywords: LEADERSHIP; INNOVATION; RESEARCH